National Delegation to the Conference of the Parties (COPs) of the United Nations Framework Convention on Climate Change (UNFCCC) - Ali, Mohammad (AIUB Journal of Business and Economics, 2019)
Although criticized on management and outcome, attendance in environmental mega conferences has been continuously increasing. Recent Conference of the Parties (COP) of the United Nations Framework Convention on Climate Change (UNFCCC) has hosted thousands of delegates. Climate vulnerable countries show similar trend in size of national delegation. Size of delegation team is positively correlated with the total population while environmental performance and political stability of the country do not influence the size of delegation team. In formation of state representatives, countries differ in their preferences to academic community, public and private sector, business community etc. Bangladesh, one of the highly climate vulnerable countries, shows some exceptions – participants from non-government organizations (NGOs) and private sectors are minimal, while political personality, irrespective of their level of expertise in relevant field, are substantial. It is proposed that UNFCCC should come up with some policy guidelines to ensure optimum assembly of academics, researcher, practitioners, government officials and private sector for countries to select delegation team for COPs.